2009
DOI: 10.1111/j.1365-2141.2009.07677.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of concurrent fludarabine and rituximab for the treatment of marginal zone lymphomas

Abstract: Summary The marginal zone lymphomas (MZLs) are a recently defined group of related diseases that probably arise from a common cell of origin, the marginal zone B cell. Data on therapy for subtypes other than gastric mucosa‐associated lymphoid tissue (MALT) lymphoma has been largely limited to retrospective case series. This prospective phase 2 study of fludarabine and rituximab for the treatment of marginal zone lymphomas enrolled 26 patients, 14 with nodal MZL, eight with MALT lymphomas and four with splenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 36 publications
3
60
0
1
Order By: Relevance
“…In this study, we did not observe the consistent rate of fatal infectious events that was reported in the LL02 trial, 22 in which such infections occurred mainly in patients aged >65 years who had splenic MZL; for this reason, we excluded these 2 categories of patients from our study. A previous phase 2 study by Brown et al 40 indicated that the combination of rituximab and fludarabine in MZL, although it had high efficacy, was associated with significant hematologic and infectious toxicity both during and after therapy. The excellent efficacy/safety ratio in our study may be explained in part by our exclusion of older patients from the study population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not observe the consistent rate of fatal infectious events that was reported in the LL02 trial, 22 in which such infections occurred mainly in patients aged >65 years who had splenic MZL; for this reason, we excluded these 2 categories of patients from our study. A previous phase 2 study by Brown et al 40 indicated that the combination of rituximab and fludarabine in MZL, although it had high efficacy, was associated with significant hematologic and infectious toxicity both during and after therapy. The excellent efficacy/safety ratio in our study may be explained in part by our exclusion of older patients from the study population.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that fludarabine has a greater activity than the other purine analogs. Excellent responses to single-agent rituximab or in combination with fludarabine or fludarabine and cyclophosphamide or cladribine have been documented [19,20,[39][40][41]. It is unknown whether chemotherapy plus rituximab is a better option than single-agent rituximab.…”
Section: Management and Treatment Of Smzl Early Versus Late Interventimentioning
confidence: 99%
“…It is unknown whether chemotherapy plus rituximab is a better option than single-agent rituximab. Potential side effects of the purine analogs need to be taken into account, particularly in the elderly population or in patients with comorbidities [40]. Nevertheless, these schedules should be considered as front line in patients without bulky spleens and who require treatment.…”
Section: Management and Treatment Of Smzl Early Versus Late Interventimentioning
confidence: 99%
“…100 Although treatment with fludarabine and rituximab was highly effective, it came with significant toxicity that had not been observed in other lymphoma types to that extent.…”
Section: 14-18mentioning
confidence: 99%
“…9,[14][15][16][17][18] A phase II study in 26 patients with marginal zone lymphomas, mostly NMZLs, illustrated that treatment regimens in other low-grade B-cell lymphomas cannot be simply applied to MZL. 100 Although treatment with fludarabine and rituximab was highly effective, it came with significant toxicity that had not been observed in other lymphoma types to that extent.…”
Section: Treatment and Prognosismentioning
confidence: 99%